Evaluation of yeast-based additives, as an alternative to ionophores, on rumen fermentation of ruminant diets using an in vitro gas production system - Cagliari, Amanda Regina; Magnani, Elaine; Rigon, Fernanda; Loregian, Kalista Eloisa; Casagrande, Ana Claudia; Amâncio, Bruna Roberta; Bueno da Silva, Juliana; Lisboa Santos, Veronica; Marcondes, Marcos Inácio; Paula, Eduardo Marostegan; Del Bianco Benedeti, Pedro; Branco, Renata Helena (Frontiers in Animal Science, 2023)
The study aimed to evaluate the effects of yeast-based additives, as alternatives to monensin, on rumen fermentation parameters, greenhouse gases emissions, and ruminal kinetics of ruminant diets using an in vitro system. Thus, three experiments were conducted aiming the individual evaluation of increasing levels of three yeast-based additives: Exp 1) Prebiotic blend 1: yeast culture [Saccharomyces cerevisiae (Scer)], beta glucans, fructooligosaccharides, galactooligosaccharides, and mannanoligosaccharides; Exp 2) Prebiotic blend 2: beta glucans fractions, and mannanoligosaccharides from Scer; and Exp 3) Yeast cells: Hydrolyzed, inactivated and spray-dried yeast (Scer) cells. The experimental design and procedures were equal across all experiments. Thus, six treatments were evaluated within each experiment: a monensin additive as the positive control (Rumensin ® , 25mg/kg DM) and the inclusion of 0, 533, 1067, 1600, and 2133 mg/kg (DM basis) of yeast additive in ruminant diets (composed of 60% corn silage and 40% concentrate). An in vitro gas production (GP) system with 50 bottles (Ankom RF ) was used in three consecutive fermentation batches to evaluate total GP, kinetics and fermentation profiles, CH4, and CO2. The comparison of yeast additives and the monensin was performed using the Dunnett test (5%). Also, yeast additive levels were analyzed for linear and quadratic responses. For Exp. 1, the inclusion of 1600 mg/kg of yeast additive had lower concentrations of propionate, iso-butyrate, valerate, and branched-chain volatile fatty acids and greater acetate concentration than monensin. For Exp. 2, monensin had lower total VFA and iso-valerate concentrations than 1600 mg/kg of yeast additive inclusion. Also, monensin had a lower iso-valerate concentration and greater NH3-N concentration than 1067 mg/kg of yeast additive inclusion. For Exp. 3, the inclusion of 533 mg/kg of yeast additive had lower valerate and BCVFA concentrations and greater CH4 and CO2 concentrations than monensin. Also, monensin had lower total VFA, butyrate, and acetate to propionate ratio and greater propionate concentration than the 2133 mg/kg of This is a provisional file, not the final typeset article yeast additive inclusion. Overall, these results suggest that the yeast-based additives might be an alternative to monensin to improve animal nutrient use efficiency and improve livestock sustainability.